Shared social responsibility: a field experiment in pay-what-you-want pricing and charitable giving - Gneezy, Ayelet; Gneezy, Uri; Nelson, Leif D; Brown, Amber (Science (American Association for the Advancement of Science), 2010)
A field experiment (N = 113,047 participants) manipulated two factors in the sale of souvenir photos. First, some customers saw a traditional fixed price, whereas others could pay what they wanted (including $0). Second, approximately half of the customers saw a variation in which half of the revenue went to charity. At a standard fixed price, the charitable component only slightly increased demand, as similar studies have also found. However, when participants could pay what they wanted, the same charitable component created a treatment that was substantially more profitable. Switching from corporate social responsibility to what we term shared social responsibility works in part because customized contributions allow customers to directly express social welfare concerns through the purchasing of material goods.